Natural products for Gut-X axis: Pharmacology, toxicology and microbiology in mycotoxin-caused diseases - Li, K.; Wang, S.; Qu, W.; Ahmed, A.A.; Enneb, W.; Obeidat, M.D.; Liu, H.-Y.; Dessie, Tadelle; Kim, I.H.; Adam, S.Y.; Cai, D. (Frontiers Media, 2024)
Introduction: The gastrointestinal tract is integral to defending against external contaminants, featuring a complex array of immunological, physical, chemical, and microbial barriers. Mycotoxins, which are toxic metabolites from fungi, are pervasive in both animal feed and human food, presenting substantial health risks.